Cosmic Ray Variations Recorded by the CARPET Facility on March 7, 2011 - Makhmutov, V. S. (2013)
The CARPET cosmic ray detector was installed in 2006 in the Argentinean Andes at an altitude of 2550 m at the El Leoncito Astronomical Complex (CASLEO) in San Juan, Argentina (S31.8, W69.3; Rc = 9.659.65 GV). This instrument was developed at the Lebedev Physical Institute (LPI) in Russia as part of an international collaboration between the LPI, Brazil’s Mackenzie Center for Radioastronomy and Astrophysics (CRAAM), and the CASLEO. This work presents the results from analyzing variations in cos mic ray intensity recorded by the CARPET facility during the solar proton event of March 7, 2011. Also used in our analysis were the experimental data obtained by the GOES, FERMI, and ISS spacecraft during this solar event.